The Maturity Process of Pi in Life of Pi - Gracia Purnomo (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This thesis discusses the process of maturity of Pi in Life of Pi. I am curious to find out how Pi is mature from his childhood, teenager, and adulthood. Therefore, I use Erik Erikson’s theory of psychosocial development to find out the influence of the society that Pi lives in. In each stage of Pi’s development, I study his character traits and I see the outcome. In addition, I am using psychological development to find out what is inside Pi’s mind and what is his way of thinking. Throughout the process, Pi faces some obstacles or psychosocial crisis from his surroundings especially from his father and friends in his childhood and early teenager years. However, because of the obstacles from his surroundings, Pi becomes mature in taking his actions and decisions. In addition, Pi faces a big situation that is surviving in the sea with Richard Parker. I can see from this experience, Pi finds his identities that are self-acceptance, compassion, patience, honesty, gratitude, self-control, accountability, open-mindedness, and humility. Despite the hardship from his childhood and teenage years, Pi manages to be emotionally mature. As a result, Pi is indeed mature in his life and it can be seen in his adulthood. Pi has an intimate relationship with his wife and children. Keywords: Maturity Process, Identity, Role Confusion, Adulthood, Life of Pi